Identification and organ-specific patterns of expression of two metallothioneins in the sentinel species Gammarus fossarum - Degli Esposti, Davide; Lalouette, Auréline; Gaget, Karen; Lepeule, Louveline; Chaabi, Zineb; Leprêtre, Maxime; Espeyte, Anabelle; Delorme, Nicolas; Quéau, Hervé; Garnero, Laura; Calevro, Federica; Chaumot, Arnaud; et al. (Comparative Biochemistry and Physiology Part B Biochemistry and Molecular Biology, 2024)
Metal pollution is a major concern for aquatic environments. Widespread contamination by various trace metal ions has been described in freshwater streams as well as their subsequent bioaccumulation, potentially leading to toxicity and trophic transfer. Metallothioneins constitute an evolutionary conserved family of low molecular weight, cysteine-rich, metal-chelating proteins, whose known physiological functions are the maintenance of the homeostasis of essential metals, the detoxification of non-essential metals, and the protection against oxidative stress and free radicals. In this study, we identified two metallothionein-coding transcripts, mt1 and mt2, in the transcriptome of the amphipod Gammarus fossarum, a sentinel species widely used to assess the quality of watersheds. For the first time, we investigated the organ-specific patterns of expression of these two mt transcripts at the individual level in the gills and the caeca of this small crustacean. In silico analysis and experimental exposures to environmentally relevant concentrations of cadmium, zinc and silver showed that G. fossarum mt1 induction is stronger after Cd exposure compared to the other tested metals. G. fossarum mt1 was more significantly induced in the caeca than in the gills of exposed organisms for any metal exposure, while G. fossarum mt2 was, at least at the individual level, more inducible in the gills than in the caeca of G. fossarum exposed to Cd and Zn. Our results provide new genetic resources that will help to improve the understanding of metal homeostasis in this sentinel species.Metal pollution is a major concern for aquatic environments. Widespread contamination by various trace metal ions has been described in freshwater streams as well as their subsequent bioaccumulation, potentially leading to toxicity and trophic transfer. Metallothioneins constitute an evolutionary conserved family of low molecular weight, cysteine-rich, metal-chelating proteins, whose known physiological functions are the maintenance of the homeostasis of essential metals, the detoxification of non-essential metals, and the protection against oxidative stress and free radicals. In this study, we identified two metallothionein-coding transcripts, mt1 and mt2, in the transcriptome of the amphipod Gammarus fossarum, a sentinel species widely used to assess the quality of watersheds. For the first time, we investigated the organ-specific patterns of expression of these two mt transcripts at the individual level in the gills and the caeca of this small crustacean. In silico analysis and experimental exposures to environmentally relevant concentrations of cadmium, zinc and silver showed that G. fossarum mt1 induction is stronger after Cd exposure compared to the other tested metals. G. fossarum mt1 was more significantly induced in the caeca than in the gills of exposed organisms for any metal exposure, while G. fossarum mt2 was, at least at the individual level, more inducible in the gills than in the caeca of G. fossarum exposed to Cd and Zn. Our results provide new genetic resources that will help to improve the understanding of metal homeostasis in this sentinel species.